Exploring Emerging Bilingual Competence among Indonesian EFL University Students: An Integrated Perspective on Linguistic Development and Cognitive Regulation - Mila Adela; Moh. Iqbal Firdaus; Nargis (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
Emerging bilingual development among EFL learners involves both linguistic development and cognitive regulation during communication. However, previous studies have often examined these dimensions separately, particularly in Indonesian higher education contexts. Understanding the interaction between linguistic and cognitive development is important because bilingual learning involves not only language proficiency but also attentional regulation and communication management. This study investigates how linguistic competencies and cognitive regulation interact in the development of emerging bilingual competence among Indonesian EFL university students, addressing the limited integration of linguistic and cognitive perspectives in bilingual development research. This study employed a qualitative multiple case study approach involving 15 EFL students representing different proficiency levels. Data were collected through interviews, classroom observations, and documentation and analyzed thematically. The findings revealed differences in both linguistic and cognitive development across participant groups. Beginner learners demonstrated stronger first-language influence, pronunciation difficulties, limited vocabulary, and simplified grammatical structures. Intermediate learners showed improved grammatical awareness and communicative flexibility, although inconsistencies remained during spontaneous communication. More advanced learners demonstrated greater syntactic complexity, semantic flexibility, and confidence in communication, although traces of first-language influence persisted. Across participant groups, attentional regulation, working memory, and language control played important roles in supporting vocabulary retrieval, communication management, and language production. The findings imply that EFL instruction should incorporate proficiency-sensitive strategies and cognitive support to facilitate emerging bilingual development among university learners. However, the findings should be interpreted within the context of the study’s small sample size, qualitative design, and the absence of standardized proficiency measures